Using station and mean‐sea‐level pressure values in SYNOP reports to recover, or correct, barometer elevation information. (27th December 2021) - McGrath, Ray
Abstract : Missing or erroneous station metadata are often a source of error in determining the reference level for the reported station pressure in conventional land‐based weather reports: the reported pressure may be inconsistent with any reported mean‐sea‐level pressure, limiting the usefulness of the data for climate or operational forecasting work. Historical Irish observations are used to highlight the issue and demonstrate how changes in the barometer elevation height may be detected and accurately estimated.